EFEK INTERAKSI PEMBERIAN SILIKAT DAN MIKORIZA PADA ANDISOL TERHADAP P-TERSEDIA DAN PERTUMBUHAN TANAMAN JAGUNG (Zea mays L.) - Nurmaya Ginting; Lahuddin Musa; Bintang Sitorus (Jurnal Agroekoteknologi, 2013)
The objective of this research is to know the interaction effects of Silicate and Mycorrhizaapplication to Andisol on the phosphorus and maize growth. The experiment was conducted at thescreen house, at Laboratory of Chemistry and Soil Fertility, and Research and TechnologyLaboratory, Faculty of Agriculture, University of North Sumatera, Medan from July until December2012 . Andisol soil was taken from horticultural farms at Kuta Rakyat Village, Naman Teran Subdistrict, Karo District. The design used was Randomized Block Design (RBD) with 3 replicationand 2 (two) factors, namely Silicate (Si) consists which of 5 level: Si0(control), Si1(0.89 g/4 kg soil)Si2(1.78 g/4 kg of soil), Si3(2.67 g/4 kg soil), Si4(3.56 g/4 kg soil) and Mycorrhiza factor (Mi),which consists of three levels, that is: Mi0 (0 g/4 kg soil), Mi1(15 g/4 kg soil) Mi2(30 g /4 kg soil)and 3(three) replication to meet 45 experimental units. The results of this research showed thatapplication of Silicate on Andisol without mycorrhizal and higher dosage did not increase Pabsorptionand corn growth, while Silicate application at medium dosage (15 g/4 kg soil) increasedP-Available, P-absorption and corn growthKeywords: andisols, silicate, mycorrhiza and P-available